Perancangan User Experience Aplikasi Mobile Pengelola Toko Kue menggunakan Pendekatan Design Thinking (Studi Kasus: UMKM Dapur Maya di Pangkalpinang) - Muhammad Hafiizul Kirom; Riswan Septriayadi Sianturi; Agi Putra Kharisma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
MSMEs play an important role in the country's economy. MSMEs have great potential, therefore it is important to help MSMEs maximize their potential. MSMEs generally have not adapted to modern ways of managing businesses. Dapur Maya is one of them. Dapur Maya still uses the traditional method of using pen and paper or memorizing in most of its management aspects. This causes problems such as customer complaints due to late orders or forgetting to buy some ingredients which lead to decreased customer trust and revenue. To help Dapur Maya MSMEs and similar MSMEs solve this problem, research was done to design the user experience of a mobile application for cake shop management using the Design Thinking method. The design goes through empathise, define, ideate, prototype, and test phase. The test results show an effectiveness level of 92%, an efficiency level of 0.22 goals/second, and a SUS score of 81.6 which can be rated as Good, B grade scale, and Acceptable category. The results of UEQ testing gave 1.57 on Attractiveness, 2.10 on Perspicuity, 2.20 on Efficiency, 1.95 on Dependability, 1.80 on Stimulation, and 1.20 on Novelty. All UEQ scores are greater than 0.8 which means the results are considered positive.